Enantioselective Double Manipulation of Tetrahydroisoquinolines with Terminal Alkynes and Aldehydes under Copper(I) Catalysis1. (29th November 2013) - Lin, Weilong; Cao, Tao; Fan, Wu; Han, Yulin; Kuang, Jinqiang; Luo, Hongwen; Miao, Bukeyan; Tang, Xinjun; Yu, Qiong; Yuan, Weiming; Zhang, Jiasheng; Zhu, Can; et al.
Abstract Tetrahydroisoquinoline alkaloids with a C1 stereogenic center are a common unit in many natural and non‐natural compounds of biological importance. Herein we describe a novel CuI‐catalyzed highly chemo‐ and enantioselective synthesis of chiral tetrahydroisoquinoline‐alkaloid derivatives from readily available unsubstituted tetrahydroisoquinolines, aldehydes, and terminal alkynes in the presence of the ligand (R, R)‐N‐pinap. This synthetic operation installs two substituents in the 1‐ and 2‐positions.